International single window environment: Prospects and challenges - Abhinayan Basu Bal; Trisha Rajput; Parviz Alizada (Asian Development Bank Institute (ADBI), 2017)
Efforts of various international institutions have supported implementation of national/regional single windows and the next logical step would be to internationalize and make them interoperable to allow for greater collaborative information sharing. The purpose of this paper is to review the legal framework necessary for implementing international single window environment (ISWE) and, in that context, examine particular economic and financial aspects of the current developments. The discussion shows that ISWE is desirable as it may contribute towards creating a level playing field for SMEs participating in global supply chains. The paper discusses ASEAN Single Window to identify prospects and challenges, and highlight the legal and economic viability of interoperability. ASW is examined from transaction cost and information asymmetry theory perspectives to provide a methodology for conducting empirical analysis at country-level. Based on the findings the paper argues that full potential of ISWE can be realised through integration of transport and commercial requirements thereby improving G2G, B2G and B2B information flows. Nevertheless, such integration would require the ability to capture the complex relationships between various transport actors from legal and technical standpoints. To illustrate this legal complexity from transport and e-commerce law angle, the disadvantageous position of SMEs vis-à-vis use of electronic bills of lading and access to supply chain finance is examined. A critical analysis of selected legal texts is made through the lens of recent developments such as distributed ledger and cloud technologies to suggest solutions for SMEs. The conclusion highlights that transport and commercial requirements in the ISWE has to be incorporated through laws made for e-commerce and not through a piecemeal approach that replicate the functions of paper documents in an electronic environment.
Keywords: F13; P45; 330; single window; SME; ASEAN single window; transport single window; supply chain finance; electronic bill of lading; international single window environment